2018
DOI: 10.1186/s13018-018-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of type 2 diabetes mellitus on lumbar disc degeneration: a retrospective single-center study

Abstract: BackgroundDiabetes mellitus (DM) and low back pain which is mainly caused by degeneration of the intervertebral discs (IVDs) both are major public health problem worldwide. The present study was designed to investigate the association between type 2 diabetes mellitus (T2D) and severity of lumbar disc degeneration (LDD).MethodsWe retrospectively reviewed patients with low back pain visiting our spine clinic in 2014. Low back pain patients all have the lumbar MRI imaging and no previous treatment. One hundred fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 23 publications
(29 reference statements)
3
41
0
7
Order By: Relevance
“…Intervertebral disc degeneration (IVDD) is known to contribute to low back pain (1), which is the leading cause of disability around the world (2,3). Studies from different groups including ours have shown that diabetes mellitus, especially type 2 diabetes (T2D), is a major risk factor for IVDD (4)(5)(6)(7). Animal study demonstrated that extracellular matrix (ECM) metabolism in nucleus pulposus (NP) was influenced by diabetes (8), and this phenomenon was further confirmed in human samples (9); however, how diabetes affects ECM metabolism in NP is still not clear.…”
mentioning
confidence: 89%
“…Intervertebral disc degeneration (IVDD) is known to contribute to low back pain (1), which is the leading cause of disability around the world (2,3). Studies from different groups including ours have shown that diabetes mellitus, especially type 2 diabetes (T2D), is a major risk factor for IVDD (4)(5)(6)(7). Animal study demonstrated that extracellular matrix (ECM) metabolism in nucleus pulposus (NP) was influenced by diabetes (8), and this phenomenon was further confirmed in human samples (9); however, how diabetes affects ECM metabolism in NP is still not clear.…”
mentioning
confidence: 89%
“…Many evidences showed that diabetes mellitus (DM) is a dependent risk factor in the progression of IVDD . Previous epidemiological investigations have reported that DM patients have a higher incidence of IVDD than the patients without DM, and that DM patients with IVDD are also much younger than non‐DM patients .…”
Section: Introductionmentioning
confidence: 99%
“…По некоторым данным, соотношение диагностированной патологии к невыявленной оценивается как 1:2. В старших возрастных группах распространенность сахарного диабета (СД) вместе с преддиабетом составляет около 50% [4].…”
unclassified
“…Результаты анализа данных эпидемиологических исследований [6,7] свидетельствуют, что дегенеративно-дистрофические поражения позвоночника, как и другие заболевания опорно-двигательного аппарата, чаще встречаются у больных СД2. В литературе описан пациент с восемью грыжами межпозвонковых дисков (МПД) без каких-либо других факторов риска, кроме СД [4]. В среднем распространенность боли в спине у пациентов с СД2 примерно в 2 раза выше, чем в аналогичной по возрасту и полу контрольной группе [6].…”
unclassified
See 1 more Smart Citation